Magnesium Alloys Properties in Solid and Liquid States - Czerwinski, Frank (IntechOpen, 2014)
Magnesium alloys with their unique physical and chemical properties are important candidates for many modern engineering applications. Their density, being the lowest of all structural metals, makes them the primary choice in global attempts aimed at reducing the weight of transportation vehicles. However, magnesium also creates challenges at certain stages of raw alloy melting, fabrication of net-shape components and their service. The first one is caused by very high affinity of magnesium to oxygen, which requires protective atmospheres increasing manufacturing cost and heavily contributing to greenhouse gas emissions. The second challenge relates to very high corrosivity of liquid magnesium towards materials it contacts. This imposes restrictions on the selection of materials used to contain, transfer or process molten magnesium during manufacturing operations. A mixture of unique benefits and serious challenges of magnesium alloys in solid and liquid states described here makes the book very useful for a broad audience of scientists and engineers from academia and industry.